1980
DOI: 10.1029/jb085ib09p04863
|View full text |Cite
|
Sign up to set email alerts
|

Isotope geochemistry of water in Gulf Coast salt domes

Abstract: Water found as active leaks and isolated pools in the Weeks Island, Jefferson Island, and Belle Isle salt mines of south Louisiana has δ18O values ranging from −4 to +11.5‰ and δD values from −2.3 to −53‰. One sample from Weeks Island and one from Jefferson Island are isotopically similar to local surface waters and are clearly of meteoric origin. All other samples are too enriched in 18O to be meteoric waters. In the Weeks Island mine the isotopic data define a linear array given by δD = 3.0δ18O ‐ 40.1. Activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…This result is consistent with Knauth et al (1980). However, two samples (1 and 2) have been little changed from the original ^^Cl content, suggesting a relatively short residence time.…”
Section: The Use Of Bomb-tritium As An Indication Of Rapid Groundwatesupporting
confidence: 93%
See 1 more Smart Citation
“…This result is consistent with Knauth et al (1980). However, two samples (1 and 2) have been little changed from the original ^^Cl content, suggesting a relatively short residence time.…”
Section: The Use Of Bomb-tritium As An Indication Of Rapid Groundwatesupporting
confidence: 93%
“…On the basis of brine geochemistry and and ^^O composition,Kumar and Martinez (1978) andKnauth et al (1980) concluded that the fluids in Louisiana salt domes were most likely entrapped during the salt's diaphic rise as it pushed through the overlying formations. Knauth et al further suggested that the isotopic data indicate a residence time in the salt of 10-13 Ma.…”
mentioning
confidence: 97%
“…Fluid δ 18 O values exceeding 10 per mil for the ore fluids are unrealistic for basinal brines even where the brines have interacted with rock packages that include 18 O-rich phases such as marine carbonates and carbonate cements (e.g., Clayton et al, 1966;Knauth et al, 1980;Longstaffe, 1989;Taylor, 1997). Basinal brines become enriched in 18 O primarily through fluid-rock interaction; the extent of the enrichment depends on temperature, the fluid/rock ratio, and the initial oxygen isotope composition of the fluid and the exchanging mineral phases.…”
Section: Stable Isotope Analyses Of Diagenetic Phasesmentioning
confidence: 99%
“…The stable isotope data suggests that significant interactions between the Hormoz Salt and the ambient brines occurred at depth (c.f. Knauth et al, 1980;Land et al, 1988). Stable isotope analyses of brines in salt deposits in Louisiana led Knauth et al (1980) to conclude that basinal fluids were able to penetrate the salt at depths greater than 3 to 4 km.…”
Section: Oxygen Isotopes and Temperaturesmentioning
confidence: 99%
“…Knauth et al, 1980;Land et al, 1988). Stable isotope analyses of brines in salt deposits in Louisiana led Knauth et al (1980) to conclude that basinal fluids were able to penetrate the salt at depths greater than 3 to 4 km. Salt deposits have in the past been thought of as impermeable to brines and hydrocarbons.…”
Section: Oxygen Isotopes and Temperaturesmentioning
confidence: 99%